Adjuvant Chemotherapy Is Associated with Improved Survival after Esophagectomy without Induction Therapy for Node-Positive Adenocarcinoma. Issue 1 (January 2015) - Speicher, Paul J.; Englum, Brian R.; Ganapathi, Asvin M.; Mulvihill, Michael S.; Hartwig, Matthew G.; Onaitis, Mark W.; D'Amico, Thomas A.; Berry, Mark F.
Abstract : Background: This study investigated adjuvant chemotherapy (AC) use after esophagectomy without induction therapy for node-positive (pN+) adenocarcinoma using the National Cancer Database, including the impact of complications related to surgery (CRS) on outcomes. Methods: Predictors of AC use in 1694 patients in the National Cancer Data Base who underwent R0 esophagectomy from 2003–2011 without induction therapy for pN+ adenocarcinoma of the middle or lower esophagus and survived more than 30 days were identified with multivariable logistic regression. The impact of AC on survival was estimated using Kaplan–Meier and Cox-proportional hazards methods. Results: AC was given to 874 of 1694 (51.6%) patients; 618 (70.7%) AC patients received radiation. Older age (adjusted odds ratio [AOR] 0.58/decade, p < 0.001), longer travel distance (AOR 0.78 per 100 miles, p = 0.03) and CRS (AOR 0.45, p < 0.001) predicted that AC was not used. Patients given AC had better 5-year survival than patients not given AC (24.2% versus 14.9%, p < 0.001), and AC use predicted improved survival in multivariate analysis (hazard ratio 0.67, p = 0.008). Receiving radiation in addition to AC did not improve survival ( p = 0.35). Although CRS was associated with worse survival, patients who had CRS but received AC had superior survival compared to patients who did not have CRS or get AC ( p = 0.016). Conclusions: AC after esophagectomy is associated with improved survival but was only used in half of patients with pN+ esophageal adenocarcinoma. We also found that the addition of radiation to AC was not associated with a survival benefit. CRS predict worse long-term survival and lower the chance of getting AC, but even patients with CRS had improved survival when given AC.